A segmented load spectrum model for high-speed trains and its inflection stress as an indicator for line quality. (July 2021) - Yuan, Zheng; Chen, Xianjia; Ma, Lijun; Li, Qiang; Sun, Shouguang; Wei, Yujie
Graphical abstract: Highlights: Load spectra of bogie frames of high-speed trains exhibit a segmented characteristic. A novel segmented Weibull distribution model with high accuracy is proposed. The inflection stress can be adopted as an effective indicator of line conditions. Abstract: Load spectrum plays a pivotal role for fault diagnosis and reliability evaluation. Here we performed long-term field tests to investigate the characteristics of load spectra of the bogie frame in a high-speed train. With increasing steps of classifications, we reveal an apparent segmented feature of the load spectrum. We propose a new theoretical model, a segmented Weibull distribution, to describe this new characteristic. Contrast to existing models, the inflection stress in our segmented Weibull model can be employed to describe the quality of lines, and the directly parameterization for the load spectrum - line quality relationship is hardly seen in existing literature. These findings reported here are in generally applicable to other dynamic systems where fatigue failure is of paramount importance.